Artificial intelligence as a legal category: doctrinal approach to formulating a definition - I. R. Begishev; E. Yu. Latypova; D. V. Kirpichnikov (Russian Journal of Economics and Law, 2020)
Objective: to conduct a critical analysis of the existing definitions of artificial intelligence and develop an authors’ version of the concept acceptable for legal sciences.Methods: the methodological basis of the study is a set of scientific cognition methods, including abstract-logical method, comparison and correlation analysis.Results: the main regularities of decision-making by artificial intelligence are identified; the mechanism of its perception of objective reality is determined; the fundamental ability of machine learning to conform its behavior to socially acceptable processes is confirmed. It is assumed that there are many ways to describe artificial intelligence: by indicating the action mechanism, the basic operation principles, the range of tasks to be solved, etc. However, the most convincing and consistent is position of those researchers who tend to describe the AI phenomenon by designating its properties and characteristics. The authors state that there is no definition of “artificial intelligence” in the modern legal doctrine. As a result of a comprehensive analysis of various scientific sources in a systematic unity with own judgments, it is proposed to introduce the author’s version of the “artificial intelligence” concept into scientific circulation.Scientific novelty: the paper presents an assessment of the “artificial intelligence” concept definitions available in the scientific literature and legal framework, as well as the authors’ opinion on their relevance, comprehensiveness and topicality; there is an attempt to formulate the definition taking into account all the significant properties of artificial intelligence.Practical significance: is due to the current impossibility to apply legal norms and rules to relations involving artificial intelligence taking into account their specifics. The main provisions and conclusions of the study can be used to improve the mechanisms of legal regulation of artificial intelligence in the Russian Federation.